2015
DOI: 10.1371/journal.pone.0129783
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Interlimb Asymmetry in Patients Undergoing Simultaneous Bilateral Total Knee Arthroplasty

Abstract: Simultaneous bilateral TKA (SBTKA) has been a favored surgical solution due to reduced costs and patient suffering. The purpose of the present study was to investigate the risk factors of asymmetric recovery in patients who underwent SBTKA and whether that affected quality of life. A total of 187 patients undergoing SBTKA were included. During this study, patients underwent physical examination (knee swelling, active range of motion (ROM) of knee and quadriceps strength) and completed three surveys (VAS pain r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…active ROM, quadriceps strength, and visual analogue scale pain score) between sides in simultaneous bilateral TKA has previously been examined and shown to be associated with risk factors such as female gender, old age, high BMI, high levels of anxiety, diagnostic differences, and different component sizes. We did not analyse these variables in our study; rather we focused on femoral component sizes [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…active ROM, quadriceps strength, and visual analogue scale pain score) between sides in simultaneous bilateral TKA has previously been examined and shown to be associated with risk factors such as female gender, old age, high BMI, high levels of anxiety, diagnostic differences, and different component sizes. We did not analyse these variables in our study; rather we focused on femoral component sizes [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies, particularly Yang et al, reported that asymmetrical active ROM, quadriceps strength, and visual analogue scale (VAS) pain score in simultaneous BTKA with component asymmetry are associated with risk factors such as old age, female gender and high BMI. 27…”
Section: Tablementioning
confidence: 99%